Bloody Roots

Algebra Level 3

Consider a function f ( x ) f(x) such that f ( 2 ) = f ( 6 ) = 0 f(2)=f(6)=0 . Evaluate the sum of all right sentences.

(1) f ( x ) = k ( x 2 8 x + 12 ) , k Z f(x) = k(x^2 - 8x + 12), k \in \mathbb{Z}

(2) f ( 1 ) f ( 7 ) 0 f(1) \cdot f(7) \geq 0

(4) f ( f ( 2 ) ) = f ( f ( 6 ) ) f(f(2)) = f(f(6))

(8) f ( 4 ) C f(4) \in \mathbb{C}

(16) If k k ( ) = 2 \displaystyle k^{ \displaystyle k^{ ( \cdots) }} = 2 , then f ( 4 ± k 2 ) = 0 f(4 \pm k^2) = 0 .

(32) f ( 2014 ) ( x ) = k , k R f^{(2014)}(x) = k, k \in \mathbb{R}


The answer is 16.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

(1) - Consider the function f ( x ) = log ( ( x 2 ) ( x 6 ) + 1 ) f(x) = \log((x-2)(x-6) + 1) . Notice it yields our desired roots without being a quadratic.

(2) - Consider the function f ( x ) = ( x 2 ) 2 ( x 6 ) f(x) = (x-2)^2 (x-6) . We have that f ( 1 ) f ( 7 ) = 5 f(1) \cdot f(7) = -5 has a negative value.

(4) - Consider the function f ( x ) = ( x 2 ) ( x 6 ) x f(x) = \dfrac{(x-2)(x-6)}{x} . f ( 0 ) f(0) is not defined, and the equality does not hold.

(8) - Consider the function f ( x ) = ( x 2 ) ( x 6 ) x 4 f(x) = \dfrac{(x-2)(x-6)}{x-4} . f ( 4 ) f(4) is not defined, and thus it cannot be a complex number.

(16) - Solving the infinite exponentiation, we find k = 2 k = \sqrt{2} , and it yields f ( 2 ) = f ( 6 ) = 0 f(2) = f(6) = 0 , which is true.

(32) - Consider the function f ( x ) = log ( ( x 2 ) ( x 6 ) + 1 ) f(x) = \log((x-2)(x-6) + 1) . Its n n -th derivative, no matter how big n n is, never reaches a constant.

Wow....I limited my thinking to a quadratic :(

Tanya Gupta - 7 years ago

Log in to reply

That's the catch I intended to make when designing this question!

Guilherme Dela Corte - 6 years, 11 months ago

For (1), (2), (4), (8), you might as just just define the function to be

f ( x ) = ( 2 , 0 ) , ( 6 , 0 ) . f(x) = (2,0), (6,0 ).

Calvin Lin Staff - 6 years, 5 months ago

For 16, we can just substitute the given equation to itself to yield k 2 = 2 k^2=2 .

Kenny Lau - 6 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...